THE INFLUENCE OF ENVIRONMENTAL COSTS AND PERFORMANCE ENVIRONMENT ON FINANCIAL PERFORMANCE - Nareswari, Adyandra Sabrina; Ramdani, Safier; Larasati, Meita (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the impact of environmental costs and environmental performance on financial performance. Environmental costs, including expenditures for natural resource management, emission control, and waste management, are hypothesized to influence profitability. Meanwhile, environmental performance, which reflects the extent to which companies implement corporate social responsibility (CSR) principles, is analyzed for its effect on financial results. Method: The study employs a quantitative approach using regression analysis to investigate the relationships between environmental costs, environmental performance, and financial performance. The population consists of non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the period 2022- 2023. Using purposive sampling, 98 companies were selected based on specific criteria. Results: This suggests that companies investing in sustainability and environmental initiatives can achieve long-term financial benefits. Novelty: This study highlights the relationship between environmental factors and financial outcomes within the context of non-cyclical consumer companies in Indonesia, a sector that has received limited attention in prior research. The results underscore the importance of integrating environmental sustainability into corporate strategies to enhance financial performance.